2021
DOI: 10.3389/fmed.2021.788250
|View full text |Cite
|
Sign up to set email alerts
|

Management of Endothelial Dysfunction in Systemic Sclerosis: Current and Developing Strategies

Abstract: Systemic Sclerosis (SSc) is an autoimmune disease marked by dysregulation of the immune system, tissue fibrosis and dysfunction of the vasculature. Vascular damage, remodeling and inadequate endothelial repair are hallmarks of the disease. Since early stages of SSc, damage and apoptosis of endothelial cells (ECs) can lead to perivascular inflammation, oxidative stress and tissue hypoxia, resulting in multiple clinical manifestations. Raynaud's phenomenon, edematous puffy hands, digital ulcers, pulmonary artery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 209 publications
0
29
0
1
Order By: Relevance
“…Indeed, peripheral microvasculopathy can be easily observed with NVC, a non-invasive technique that is included in the 2013 ACR/EULAR recommendations for the diagnosis and management of SSc that allows both the qualitative and quantitative evaluation of the microcirculation, thus enabling early detection of abnormalities [ 23 , 31 , 32 ]. Notably, plenty of literature indicates that NVC changes in SSc patients are often accompanied by abnormal levels of angiogenic/angiostatic factors acting on endothelial cells, some of which have been proposed as vascular biomarkers [ 4 , 33 , 34 ]. In recent years, increasing studies have demonstrated that endothelial cells express neuropilins, plexins, and roundabouts, all axon guidance molecule receptors that interact with their soluble neuroendothelial ligands, such as semaphorins and slits, to control endothelial cell sprouting and angiogenesis [ 9 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, peripheral microvasculopathy can be easily observed with NVC, a non-invasive technique that is included in the 2013 ACR/EULAR recommendations for the diagnosis and management of SSc that allows both the qualitative and quantitative evaluation of the microcirculation, thus enabling early detection of abnormalities [ 23 , 31 , 32 ]. Notably, plenty of literature indicates that NVC changes in SSc patients are often accompanied by abnormal levels of angiogenic/angiostatic factors acting on endothelial cells, some of which have been proposed as vascular biomarkers [ 4 , 33 , 34 ]. In recent years, increasing studies have demonstrated that endothelial cells express neuropilins, plexins, and roundabouts, all axon guidance molecule receptors that interact with their soluble neuroendothelial ligands, such as semaphorins and slits, to control endothelial cell sprouting and angiogenesis [ 9 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Peripheral microvascular tone dysregulation, manifesting with Raynaud’s phenomenon (RP), as well as microcirculatory abnormalities, mirrored by nailfold capillaroscopic changes, represent the earliest clinical manifestations of SSc and may precede both cutaneous and organ fibrosis by months or years [ 1 , 2 , 3 ]. Such a microvascular dysfunction is characterized by vascular repair impairment and defective angiogenesis culminating in capillary network disruption, and frequently leads to significant peripheral ischemic manifestations such as digital ulcers (DUs) [ 4 , 5 ]. SSc-related ischemic DUs are disabling and painful lesions that are often refractory to treatment and may result in severe complications including infections and gangrene, thus heavily compromising patients’ quality of life [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vascular endothelial dysfunction is caused by EC injury, apoptosis, defective angiogenesis and vasculogenesis, EndoMT, and excessive coagulation, leading to perivascular inflammation, tissue hypoxia, oxidative stress induction, myofibroblast accumulation, hypertension, fibrin deposition, and PARs activation [ 155 , 156 , 157 ].…”
Section: Vascular Endothelial Dysfunction In Fibrosismentioning
confidence: 99%
“…Clinicians should perform a critical evaluation of the patients’ clinical status, in terms of blood pressure control, extrarenal disease manifestations, and comorbidities ( 8 , 9 ). Some case reports showed that the administration of endothelin-1 antagonists (i.e., bosentan) may ameliorate the outcome of patients with SRC who were experiencing worsening renal function and rapid necessity of RRT despite the use of ACEis ( 55 , 56 ). Recently, a phase II randomized placebo-controlled trial reported the possible role of a highly selected endothelin-A antagonist, zibotentan, in stabilizing the eGFR trend, without a rebound of hypertension after the interruption of the drug ( 57 ).…”
Section: The Timing Of Kidney Transplantationmentioning
confidence: 99%